Kepala Sekolah sebagai Katalisator Keberhasilan Inovasi dalam Pendidikan - Faiz Lihubbil Ahmadi; Ilham Syah; Wilda Muhib Muttaqin; Tamrin Fathoni (Tamilis Synex: Multidimensional Collaboration, 2024)
Study of the role of school principals begins with school/madrasah principals standards contained in Permendiknas No. 13 of 2007. There are two aspects, qualification and competence as initial capital as principal. Capital owned by the school principal should be encouraged to five role as an effective leader. The fifth role is as a catalyst for an exciting, visionary motivator, link control, implementing a firm and wise experts. This role serves to grow the value of the character at the school, where there are eighteen value character implemented in all learning activities in schools. The purpose of this study was to explore how the principal should work at school. Six efforts can be implemented by school principal in enhancing the teacher’s performance including (1) to focus seriously on the improvement of teacher competencies, (2) to provide sufficient funding for improving teacher professionalism, (3) to supervise and guide teachers professionally, (4) to create a organizational culture of school that are comfortable for teachers, (5) to create innovation and advancement at school, and (6) to provide various rewards for each achievement that are done by teacher. Hence, it is recommended that school principal must more actively and creatively collaborate with teachers and educational stakeholder to conduct the improvement of teachers’ performance.